Bukan Hanya Tempat Mencari Informasi, Tetapi Tempat Berbagi Pengetahuan: Studi Kasus di Perpustakaan Chandra Widodo - Supriatna, Neka Rusyda (Jurnal Ilmu Informasi, Perpustakaan, dan Kearsipan, 2018)
This research was conducted using a qualitative research with a case study method in one of the special libraries in South Jakarta, namely the Chandra Widodo library. The result of this study is that in fact various kinds of inter-library activities such as discussion, book review, and seminars in the library are examples of knowledge sharing activities. In other words, the library becomes a place where the users do the process of sharing knowledge in it, not just looking for books. The result of this research is that the library becomes a common room for library users to do some kinds of knowledge sharing processes. In the future it is expected that librarians can actively participate to share librarianship information in the library. And make a book from the results of sharing knowledge, so that knowledge can be used by many people.